Evaluasi Kinerja Pemeliharaan Waterproofing Rooftop Gedung IPU Menggunakan Metode EVM (Studi Kasus: RSUD dr. Saiful Anwar): Performance Evaluation Of Rooftop Waterproofing Maintenance At The IPU Building Using The EVM Method (Case Study: RSUD dr. Saiful Anwar) - Nadine Marwa Savitri; Alfianto, Imam (Media Ilmiah Teknik Sipil, 2025)
Public construction projects often face challenges in controlling time and cost, including the maintenance project of the rooftop waterproofing of the IPU Building, 7th Floor, at RSUD Dr. Saiful Anwar, Malang City. This study aims to evaluate the project performance using the Earned Value Management (EVM) method, which integrates schedule and cost analysis to provide a comprehensive overview of project execution efficiency. The study was conducted up to the 5th week, with a work progress of 20.017%. The data used include the budget plan, S-curve, weekly reports, and actual project costs, analyzed using Microsoft Excel. The calculation results show that in the 4th week, the project experienced a cost deviation with a Cost Variance (CV) of -Rp47,228,379.15 and a schedule deviation with a Schedule Variance (SV) of -Rp16,025,142.49. The Cost Performance Index (CPI) of 0.76 indicates budget overrun, while the Schedule Performance Index (SPI) of 0.90 indicates a delay in execution. The estimated total cost at completion (EAC) is Rp939,260,546.02, exceeding the initial budget of Rp715,408,147.00, and the estimated total time for completion (EAS) is 9.42 weeks compared to the original plan of 9 weeks. These findings highlight the importance of implementing EVM to detect early project deviations and provide a quantitative basis for project performance evaluation